Review on Subsea Pipeline Integrity Management: An Operator’s Perspective - Chiemela Victor Amaechi; Grant Hosie; Ahmed Reda (Energies, 2022)
For operators of oil and gas to save the cost of unforeseen events and risks, and to avoid unnecessary shutdowns, there is a need to have an effective subsea pipeline integrity management system. Currently a large number of subsea pipelines around the globe have already exceeded their design lives; nevertheless, they are still being operated safely, effectively and with diligent consideration towards Environmental, Health and Safety regulations, as well as international standards and best practices. In addition, many older flowlines have no permanent pigging facilities due to various design and operational limitations. For the unpiggable pipeline, the vast majority of the oil and gas operators use different inspection and monitoring techniques to provide essential integrity management data such as product chemistry, cathodic protection, electrical resistance probes and coupons, etc. However, translating such essential integrity management data into meaningful information to make crucial integrity-based decisions can be challenging. This paper presents a holistic approach that implements the required pipeline integrity management tools to facilitate the safe operation and maintenance of pipeline systems going forward. This paper also provides a review of the integrity of the ageing pipelines and underlines the practical pipeline integrity management steps and systems that maintain the condition of the subsea assets going forward.